2015
DOI: 10.5430/cns.v3n4p112
|View full text |Cite
|
Sign up to set email alerts
|

Nurses and physicians point of view regarding causes of conflict between them and resolution strategies used

Abstract: Nursing is profession based on collaborative relationships with clients or patients and colleagues. Nurses who effectively deal with conflict demonstrating respect for their clients, their colleagues and the profession. This study was aimed at comparing between nurses and physicians point of view regarding causes of conflict between the first party and resolution strategies used. An analytic cross-sectional design was used in this study which was carried out in various medical departments and intensive care un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 25 publications
3
17
1
Order By: Relevance
“…Five studies reported “accommodation” as the most frequently used conflict‐management styles among nursing professionals (Akel & Elazeem, ; ; Baddar et al., ; Chris, ; Kunaviktikul, Nuntasupawat, Srisuphan, & Booth, ; Whitworth, ). Of these studies, two examined conflict‐management styles in staff nurses (Akel & Elazeem, ; Baddar et al., ) and in three studies the staff nurses and nurse managers were included as study participants (Chris, ; Kunaviktikul et al., ; Whitworth, ). For instance, Baddar et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies reported “accommodation” as the most frequently used conflict‐management styles among nursing professionals (Akel & Elazeem, ; ; Baddar et al., ; Chris, ; Kunaviktikul, Nuntasupawat, Srisuphan, & Booth, ; Whitworth, ). Of these studies, two examined conflict‐management styles in staff nurses (Akel & Elazeem, ; Baddar et al., ) and in three studies the staff nurses and nurse managers were included as study participants (Chris, ; Kunaviktikul et al., ; Whitworth, ). For instance, Baddar et al.…”
Section: Resultsmentioning
confidence: 99%
“…In dealing with conflict with doctors, nurses in Saudi Arabia with diplomas preferred to use compromising, while nurses who had a baccalaureate degree had a greater preference for the collaborative strategy (Baddar et al., ). In one study, involving nurses in Egypt, the nurses’ qualifications had a weak or negative correlation with the collaboration dimension, suggesting a lower use of collaborating styles in nurses with higher academic degrees (Akel & Elazeem, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Otherwise, such differences may lead to conflict. [5]“Conflict is a dynamic process that occurs between interdependent parties as they experience negative emotional reactions to perceived disagreements and interference with the attainment of their goals.”[6] As Brinkert noted, it is fundamentally a communication process which can potentially arise when individuals are engaged in communications with one another. Therefore, never does the conflict happen in the lack of communication.…”
Section: Introductionmentioning
confidence: 99%